#TITLE_ALTERNATIVE# - SIMANTUPANG ( NIM 15110085 ); Pembimbing : Dr. Ir. Kosasih Prijatna, M.Sc., JOSHUA
Determination of the location and the design of subsea pipelines need to consider many parameters. The parameters will be discussed in this thesis is the oceanographic data, which are tides and currents data. Design basis of subsea pipelines needs tide and current with a long duration, in order to determine the maximum value of tide and current in the location and the subsea pipeline. To address the needs of data with a long duration, modeling of ocean tides and currents are conducted. Modeling chosen because it saves the cost and time compared with measurements in the field. Modeling methods used in this study is numerical modeling, using Delft3D software. Delft3D models are based on the Navier-Stokes equations for incompressible fluid. Tide and current model in this study involves several variables, which are seafloor roughness, bathymetry, wind, and time step. The results of the modeling will be verified and calibrated based on the measurement data. The final results of the study in the form of tide and current model and two-dimensional current map. The model are used to determine the maximum current value in subsea pipeline route. The maximum current value obtained from two seasons simulations, namely summer monsoon and the eastern monsoon. The modeling results showed the differences with measurement data, calibration are conducted to reduce the differences. After calibration, the quality of the models has increased. The maximum current value obtained on eastern monsoon. Maximum current speed on subsea pipeline route based on two seasons simulation are 0.391 m/s. This value may represent the maximum condition for one year.